Front Cover. Issue 11 (4th November 2020) - Bertoncini, Andrea; Laptenok, Sergey P.; Genchi, Luca; Rajamanickam, Vijayakumar P.; Liberale, Carlo
Abstract: We present a 3D printed high‐NA catadioptric lens for forward signal collection in laser‐scanning microscopy. The lens can replace expensive and bulky high‐NA microscope objectives or condensers and is so thin to fit inside top‐stage microscope incubators. The lens is particularly beneficial in Stimulated Raman Scattering (SRS), where a high‐NA beam collection is needed to avoid artefacts due to Cross Phase Modulation. Further details can be found in the article by Andrea Bertoncini, Sergey P. Laptenok, Luca Genchi, Vijayakumar P. Rajamanickam, and Carlo Liberale (e202000219 ). Abstract : We present a 3D printed high‐NA catadioptric lens for forward signal collection in laser‐scanning microscopy. The lens can replace expensive and bulky high‐NA microscope objectives or condensers and is so thin to fit inside top‐stage microscope incubators. The lens is particularly beneficial in Stimulated Raman Scattering (SRS), where a high‐NA beam collection is needed to avoid artefacts due to Cross Phase Modulation. Further details can be found in the article by Andrea Bertoncini, Sergey P. Laptenok, Luca Genchi, Vijayakumar P. Rajamanickam, and Carlo Liberale (e202000219 ).